Nutritional and chemical composition of culinary-medicinal Royal Sun Agaricus (the Himematsutake mushroom) Agaricus brasiliensis S. Wasser et al. (Agaricomycetideae) - Menezes, Milena C. [UNESP]; Eira, Augusto F.; Silva, Giovanni Faria [UNESP]; Martins, Otavio A.; Meira, Dirceu R.; Caramori, Carlos A. [UNESP] (Begell House, 2008)
The objective of the study was to determine the nutritional and chemical composition (carbohydrates, proteins, lipids, calcium, and iron), water and ash content, and the caloric value of powdered fruiting bodies from six strains and from a mixture of strains of the culinary-medicinal mushroom Agaricus brasiliensis. The Kruskal-Wallis nonparametric and multiple comparisons tests and the Pearson correlation coefficient were used, with a 5% significance level. First, the results showed that strain 99/30 had a similar nutritional composition to the mixed sample. Second, when comparing strain nutrients to the mixture nutrients, the highest levels of carbohydrates, proteins, and calcium were in strain 99/25, and the highest levels of lipids were in strains 97/11, 99/28, and 99/30. Strain 99/30 was highest both in caloric value and moisture content. Finally, the mixture was established as a good source of macronutrients and micronutrients, and strain 99/30 was the closest to the mixture in nutritional composition. © 2008 by Begell House, Inc.
Keywords: Agaricus brasiliensis; Chemical composition; Culinary-medicinal mushrooms; Nutritive value